A prática de autolesão em jovens : uma dor a ser analisada - Barbosa, Viviane da Silva (2017)
Self-harm is an act with a non-letal outcome in which the individual performs one of the following acts: practice of behaviors intended to injure himself; ingestion of an overdose of what has been prescribed or the known therapeutic dose; ingestion of an illicit or recreational drug in an act that the person considers to be a self-harm; ingestion of substances or non-ingestible objects. Due to the variety of behaviors it was decided to investigate only the acts of cutting, burning, hitting, scratching, piercing the skin with sharp objects and poking at the skin to cause injuries. The general objective was to investigate the phenomenon of self-harm based on the meanings attributed to it by young people who experience or experienced it. The specific objectives were to identify the practice and the reasons for self-harm from the experiences of young people, to evaluate the perception of pain in young people who practice or have practiced self-harm, analyze the meanings that these young people attribute to self-harm, propose interpretative hypotheses on the reports of the young who practice or have practiced self-harm based on content analysis freudian psychoanalytic theory. A qualitative research was carried out with semi-structured interviews with young people between 18 and 28 years old who practice or practiced self-harm. Ten interviews were carried out and through content analysis seven categories were identified: "the context of self-harm", "sensations and feelings", "motives", "goal", "associated aspects", "the meanings of pain" and "described experiences". The analysis of the results was based on Freudian theory. The reported experiences related to self-harm seem to have in common the psychic suffering, the difficulties of dealing with this suffering and the need for unloading. Physical pain is cited as different from other situations and seems to contribute to the reported relief when they pratice self-harm. The speeches refer to several issues as losses, mourning, anguish, masochism, suicide/death and life. One can associate self-harm to the challenges of adolescence and the beginning of adulthood, with melancholic experiences related to the reworking of identity and sexual identity. Furthermore, the self-harm appears in the speeches as a substitute to suicide since it provides temporary relief from psychic pain, seemingly unbearable at times. Thus, self-harm appears to be a symptom which expresses intense psychic suffering. From this, further discussion on the subject is important, which should cover parents, teenagers, professionals in education and health, besides the elaboration of prevention and treatment measures.